The structure, characterization and dual-activity of exopolysaccharide produced by Bacillus enclensis AP-4 from deep-sea sediments - Hu, Xin; Li, Fengshu; Zhang, Xiuli; Pan, Yaping; Lu, Jinren; Li, Yiming; Bao, Mutai (Frontiers in Marine Science, 2022)
In recent years, the exopolysaccharide (EPS) produced by deep-sea bacteria has attracted the interest of various researchers. In the present study, we have explored the properties and structure of a novel exopolysaccharide (called BPS) produced by Bacillus enclensis AP-4 from deep-sea sediments. The maximum yield of BPS was 4.23 ± 0.17 g L−1 in a 2216E modified medium. 1H NMR studies of the purified BPS displayed α and β-configuration sugar residues, including mannose, glucosamine, glucose, galactose, and xylose in a molar ratio of 1.00: 0.09: 0.04: 0.09: 0.07. BPS showed a molecular weight of 23,434 Da and was abundant in hydroxyl and amino residues. In addition, BPS exhibited a rod-like structure with a rough surface and was dominated by C, N, and O elements. The exopolysaccharide demonstrated remarkable thermal stability, high degradation temperature, and excellent emulsification capacity compared to most reported exopolysaccharides. Moreover, BPS displayed better quenching activities against the four radicals, which provided favorable protection for the strain. Finally, the freezing experiment investigated the cryoprotective effect of BPS on E. coli and S. aureus. BPS effectively improved the cell survival ratio and maintained the activity of Na+/K+-ATPase, which facilitates culture preservation. To the best of our knowledge, our work is the first report suggesting that marine exopolysaccharide has dual-activity. This work presents the foundation for the analysis of the structure and properties of exopolysaccharides produced by deep-sea bacteria.